Influence of night soccer matches on sleep in elite players - Nédélec, M.; Dawson, B.; Dupont, G. (The Journal of Strength and Conditioning Research, 2019)
This study examined the impact of night matches on the sleep/wake behavior of elite soccer players participating in the UEFA Champions League and French Ligue 1. A mixed method approach was used, combining objective sleep assessment with wrist activity monitors, and a survey to ascertain the sleep complaints after night matches (kick off after 18:00 hours). Most players (90%) indicated worse sleep in the nights after evening matches than after training days. Objective time in bed (-01:39 hours; effect size [ES] = 1.7; p < 0.001) and total sleep time (-01:32 hours; ES = 1.4; p < 0.001) were both lower after night matches than after training days. Night matches had a marked influence on sleep quantity later that night, both objectively and subjectively. The survey revealed that players may not have appropriate methods for better managing their sleep after night matches. It is yet to be determined whether players may benefit from individualized sleep interventions in these circumstances.